2009
DOI: 10.1182/blood-2008-05-156265
|View full text |Cite
|
Sign up to set email alerts
|

Foxn1 is required to maintain the postnatal thymic microenvironment in a dosage-sensitive manner

Abstract: The postnatal thymus is the primary source of T cells in vertebrates, and many if not all stages of thymocyte development require interactions with thymic epithelial cells (TECs). The Foxn1 gene is a key regulator of TEC differentiation, and is required for multiple aspects of fetal TEC differentiation. Foxn1 is also expressed in the postnatal thymus, but its function after birth is unknown. We generated a Foxn1 allele with normal fetal expression and thymus development, but decreased expression in the postnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
275
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(300 citation statements)
references
References 45 publications
23
275
0
2
Order By: Relevance
“…1M), some of which seem to be thymic nurse cells (25). In complementary studies, we also examined whether ÎČKlotho is expressed in TECs expressing FoxN1, a transcription factor that is critical for thymopoiesis (26). To do this, we used transgenic mice harboring a fluorescent membrane dTomato/membrane EGFP (mT/mG) Cre reporter construct (27) that marks FoxN1 Cre excision by a heritable switch from membrane-targeted tdTomato expression to membrane-targeted EGFP expression.…”
Section: Significancementioning
confidence: 99%
“…1M), some of which seem to be thymic nurse cells (25). In complementary studies, we also examined whether ÎČKlotho is expressed in TECs expressing FoxN1, a transcription factor that is critical for thymopoiesis (26). To do this, we used transgenic mice harboring a fluorescent membrane dTomato/membrane EGFP (mT/mG) Cre reporter construct (27) that marks FoxN1 Cre excision by a heritable switch from membrane-targeted tdTomato expression to membrane-targeted EGFP expression.…”
Section: Significancementioning
confidence: 99%
“…34 Foxn1 levels, therefore, have significant effects on thymic phenotypes. 35 A reduction in Foxn1 expression has been shown to cause thymic compartment degeneration, a loss of specific TEC subsets and reduced T-cell production. 35 The deletion of Foxn1 inhibited the development of mature TECs and reduced the number of total thymocytes, which is observed during normal thymic aging.…”
Section: Discussionmentioning
confidence: 99%
“…35 A reduction in Foxn1 expression has been shown to cause thymic compartment degeneration, a loss of specific TEC subsets and reduced T-cell production. 35 The deletion of Foxn1 inhibited the development of mature TECs and reduced the number of total thymocytes, which is observed during normal thymic aging. 5 In our study, we chose the Foxn1 2/2 mouse as a model to investigate the biological function of MSCs in T-cell regulation.…”
Section: Discussionmentioning
confidence: 99%
“…FOXN1 is expressed in fetal thymus and postnatal TECs and its expression is progressively down-regulated with aging [15,16,[22][23][24][25]. FOXN1 is required not only for TEC development in fetal thymus, but also for maintenance of the postnatal thymus [15,16,23,24,26]. The reduced expression or induced deletion of FOXN1 resulted in reduced TEC number and a disrupted thymic microenvironment [16,18,22,24,27].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that FOXN1 induced mTEC proliferation is due, at least in part, to the enhanced expression of cyclin D1. Whether cyclin D1 and p53 are the directly or indirectly downstream target genes remains to be determined.In addition to an increased number of mature TECs, rFOXN1 treatment also increased the number of MHC II lo immature TECs.Several investigators have also shown that, in addition to maintain existing TECs, FOXN1 also regulates TEC progenitors [15,16,18,27,31], which may also contribute to the increased number of TECs. The number of ETPs was also significantly increased after rFOXN1 treatment.…”
mentioning
confidence: 99%